A first look at the phylogeny of the Myrmarachninae, with rediscovery and redescription of the type species of Myrmarachne (Araneae: Salticidae) - Edwards, G. B.; Benjamin, Suresh P. (Zootaxa, 2009)
Myrmarachne melanocephala MacLeay, 1839, type species of the genus Myrmarachne MacLeay, 1839, is rediscovered and redescribed, and a neotype is here designated. Five new synonyms of M. melanocephala are proposed: M. contracta (Karsch, 1880) [lectotype here designated], M. providens (Peckham & Peckham, 1892), M. ramosa Badcock, 1918, M. albicrurata Badcock, 1918, and M. lateralis Badcock, 1918. Myrmarachne melanocephala is shown to be a widespread species in southern Asia that mimics the ant Tetraponera rufonigra (Jerdon). Myrmarachne christae (Prószyński, 2001) and Myrmarachne galianoae (Prószyński, 2001) are transferred from Damoetas, new combinations. The latter results in a homonym with Myrmarachne galianoae Cutler, 1981: we rename the species Myrmarachne mariaelenae Edwards & Benjamin, replacement name. Further characterization of the species groups of Myrmarachne is presented, related genera are discussed, and a preliminary phylogeny of the Myrmarachninae is given.